Do wealth shocks affect health? New evidence from the housing boom - Fichera, Eleonora; Gathergood, John (Wiley, 2016)
We exploit wealth shocks arising from housing wealth gains to examine the relationship between wealth and health. In UK household panel data positive housing wealth gains lower the likelihood of home owners exhibiting a range of non-chronic health conditions with no effect on renters. For owners housing wealth gains change health behaviours: increasing use of private health care, reducing hours of work (especially for women) and increasing time dedicated to exercise. Housing wealth gains, unlike income gains, do not increase risky health behaviours such as smoking and drinking. Furthermore, house prices highly pro-cyclical. The positive health effects of housing wealth gains on home owner health over the business cycle offset the negative health effects of labour market conditions and work intensity.